A Comprehensive Analysis of Curriculum Evolution in Post-Reformation Indonesia: A Case Study of KBK, KTSP, 2013 Curriculum, and the Independent Curriculum - Euis Supianah; Muhammad Zuhdi; Bobi Erno Rusadi (Kasyafa: Jurnal Pendidikan Agama Islam, 2026)
This paper examines the development of the Indonesian education curriculum after the 1998 Reformation era, including the 2004 Competency-Based Curriculum (KBK), the 2006 School-Level Curriculum (KTSP), the 2013 Curriculum (K-13), and the Independent Curriculum. Each curriculum is analyzed based on its rationale, objectives, main characteristics, and comparisons, particularly from the perspective of implementation and its impact on improving the quality of national education. This study emphasizes that curriculum reform is both a form of adaptation to changing times and a strategic effort to improve the quality of human resources, although in practice it always faces various implementation obstacles. The main argument is developed through the presentation of characteristics and comparative analysis between curricula that show a shift in perspective, starting from a centralized system to a more decentralized management, from an emphasis on mastery of material to the development of comprehensive competencies, and from a rigid learning approach to flexibility. This article concludes that although each curriculum has a different approach, all of them lead to the same goal, namely to enlighten the life of the nation, with the Independent Curriculum seen as the pinnacle of educational efforts to humanize humans through the principle of freedom to learn.